Pathogenic and Virulence Factor Detection on Viable but Non-culturable Methicillin-Resistant Staphylococcus aureus - Jiang, Hua; Wang, Kan; Yan, Muxia; Ye, Qian; Lin, Xiaojing; Chen, Ling; Ye, Yanrui; Zhang, Li; Liu, Junyan; Huang, Tengyi (Frontiers in Microbiology, 2021)
Food safety and foodborne infections and diseases have been a leading hotspot in public health, and MRSA has been recently documented to be an important foodborne pathogen, as well as its recognition to be a leading clinical pathogen for some decades. Standard identification for MRSA has been commonly performed in both clinical settings and food routine detection, however, most of such so-called “standard” or “guideline” or “golden standard”, are incapable of detecting VBNC cells. In this study, 2 major types of Staphylococcal food poisoning (SFP), sea and seb, as well as the pvl genes, were selected to develop a cross priming amplification (CPA) method. Limit of detection (LOD) of CPA for sea, seb and pvl were 75 ng/μL, 107.5 ng/μL and 85 ng/μL, indicating that the analytical sensitivity of CPA is significantly higher than those of conventional PCR. In addition, a rapid VBNC cells detection method, designated as PMA-CPA, was developed and further applied. PMA-CPA showed significant advantages when comparing with PCR assays, in terms of rapidity, sensitivity, specificity and accuracy. Comparing with conventional VBNC confirmation methods, the PMA-CPA showed 100% accordance, which had demonstrated the PMA-CPA assays were capable of detecting different toxins in MRSA in VBNC state. In conclusion, 3 CPA assays were developed on 3 important toxins for MRSA, and in combination with PMA, the PMA-CPA assay was capable of detecting virulence gene expression in MRSA under VBNC state. Also, the above assays were further applied in real samples. As concluded, the PMA-CPA assay developed in this study was capable of detecting toxins of MRSA under VBNC state, representing for the first time on detection of toxins under VBNC state.